2020
DOI: 10.3390/antiox9090773
|View full text |Cite
|
Sign up to set email alerts
|

WIP Modulates Oxidative Stress through NRF2/KEAP1 in Glioblastoma Cells

Abstract: Due to their high metabolic rate, tumor cells produce exacerbated levels of reactive oxygen species that need to be under control. Wiskott–Aldrich syndrome protein (WASP)-interacting protein (WIP) is a scaffold protein with multiple yet poorly understood functions that participates in tumor progression and promotes cancer cell survival. However, its participation in the control of oxidative stress has not been addressed yet. We show that WIP depletion increases the levels of reactive oxygen species and reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Also, it is important to take into account the high absolute bioavailability of MB in oral formulation reported in the literature ( Walter-Sack et al, 2009 ). Therefore, another possible explanation of treatment response variability in the different types of cancer is an unequal oxidant tolerance ( Escoll et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is important to take into account the high absolute bioavailability of MB in oral formulation reported in the literature ( Walter-Sack et al, 2009 ). Therefore, another possible explanation of treatment response variability in the different types of cancer is an unequal oxidant tolerance ( Escoll et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both chemotherapy and irradiation treatment enhanced NRF2 levels in human glioma cell lines and patient samples, and the degree of NRF2 expression was associated with earlier recurrences. A more recent study was able to show that NRF2-related protumorigenic properties in gliomas are not exclusively linked to ROS regulation or metabolic adaptation but are also linked to an enhanced expression of the transcriptional coactivator TAZ belonging to the HIPPO pathway, most probably by activating functional enhancers in the regulatory regions of TAZ [ 253 ]. As an upstream regulator of NRF2-mediated ROS tolerance in malignant glioma cells, the Wiskott–Aldrich syndrome protein (WASP)-interacting protein (WIP) inhibits KEAP1, which acts as an NRF2 repressor, finally leading to reduced ROS levels and unwanted glioma cell survival [ 253 ].…”
Section: Nrf2 and Brain (Dys)functionsmentioning
confidence: 99%
“…A more recent study was able to show that NRF2-related protumorigenic properties in gliomas are not exclusively linked to ROS regulation or metabolic adaptation but are also linked to an enhanced expression of the transcriptional coactivator TAZ belonging to the HIPPO pathway, most probably by activating functional enhancers in the regulatory regions of TAZ [ 253 ]. As an upstream regulator of NRF2-mediated ROS tolerance in malignant glioma cells, the Wiskott–Aldrich syndrome protein (WASP)-interacting protein (WIP) inhibits KEAP1, which acts as an NRF2 repressor, finally leading to reduced ROS levels and unwanted glioma cell survival [ 253 ]. In summary, there is a large body of evidence that increased NRF2 levels are associated with (a) various tumour-promoting functions in malignant gliomas, (b) negative patient survival in diffuse gliomas and glioblastomas, (c) tumour cell senescence [ 254 ], and (d) resistance towards radio-chemotherapy.…”
Section: Nrf2 and Brain (Dys)functionsmentioning
confidence: 99%
“…Not surprisingly, many studies have reported pro-tumoral effects associated with these cytoprotective functions, including ROS scavenging [5], chemoresistance and radioresistance [6][7][8], metabolic reprogramming towards anabolic pathways and the pentose phosphate pathway [9], or evasion of apoptosis [10,11]. Other studies have directly linked NRF2 to key pro-tumoral pathways such as KRAS, mutant p53, the Hippo pathway, or WIP [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%